Consumo sustentável e alternativa para o consumidor: o combate ao fast-fashion - Villens, Isabela Malospírito (Universidade Federal de São Carlos, 2023)
Consumption is considered a generational inheritance, as it has been present since the beginning of humanity and, like society, it is also marked by evolutions. Linked to this, there is a need for acceptance and accessibility, which ends up sacrificing some pillars, such as the environment. Fast fashion, a production model known for its mass production, speed in production and delivery, low prices, and fast life cycles, is currently the subject of investigations, as its consumption means greater extraction of environmental resources and greater waste generation. Therefore, in order to change the scenario, companies are mobilizing to find more sustainable and accessible solutions for consumers. Thus, this study, through a descriptive research with a non-probabilistic convenience sampling technique, aimed to discover and understand the motivations of fast fashion consumers' purchasing behavior, as well as possible sustainable alternatives. The specific objectives were to identify the consumer profile, analyze the reasons for their choices, consolidate the main stores, and propose sustainable suggestions based on the literature. The results show that the majority of consumers are employed, between 20 and 30 years old, predominantly female, with a monthly income above R$1,000. The main influencing factors were the fit of the clothes and the price, while the reason for discarding them was because they no longer fit. Finally, regarding sustainability perception, there is some concern about the continuation of excessive consumption and the lack of concern about the impacts of fast fashion.
Sustainable consumption and alternative for the consumer: the fight against fast-fashion
Keywords: Acessibilidade; Consumo; Fast-fashion; Sustentabilidade; Accessibility; Consumption; Sustainability; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::RESIDUOS SOLIDOS, DOMESTICOS E INDUSTRIAIS